Stimulation-Dependent Intraspinal Microtubules and Synaptic Failure in Alzheimer's Disease: A Review. (8th March 2012) - Mitsuyama, Fuyuki; Futatsugi, Yoshio; Okuya, Masato; Kawase, Tsukasa; Karagiozov, Kostadin; Kato, Yoko; Kanno, Tetsuo; Sano, Hirotoshi; Nagao, Shizuko; Koide, Tadashi
Abstract : There are many microtubules in axons and dendritic shafts, but it has been thought that there were fewer microtubules in spines. Recently, there have been four reports that observed the intraspinal microtubules. Because microtubules originate from the centrosome, these four reports strongly suggest a stimulation-dependent connection between the nucleus and the stimulated postsynaptic membrane by microtubules. In contrast, several pieces of evidence suggest that spine elongation may be caused by the polymerization of intraspinal microtubules. This structural mechanism for spine elongation suggests, conversely, that the synapse loss or spine loss observed in Alzheimer's disease may be caused by the depolymerization of intraspinal microtubules. Based on this evidence, it is suggested that the impairment of intraspinal microtubules may cause spinal structural change and block the translocation of plasticity-related molecules between the stimulated postsynaptic membranes and the nucleus, resulting in the cognitive deficits of Alzheimer's disease.